Strengthening the livelihoods of rural women through polyculture of carps in seasonal ponds - De, Himansu Kumar; Chattopadhyay, D. N.; Radheyshyam, Radheyshyam; Saha, G. S.; Dash, A. K.; Pal, S.; Satpati, T. S. (Indian Journal of Fisheries, 2012)
The investigation was carried out with an objective to disseminate the technology of carp polyculture among rural womenin Boudh District of Odisha to strengthen their livelihood. Polyculture of carps was demonstrated in four seasonal pondscovering 9.5 ha of water spread area through participatory approach. Mixed fingerlings of Labeo rohita, Catla catla, Cirrhinusmrigala, Cyprinus carpio and Ctenopharyngodon idella were stocked @ 6500 fingerlings ha-1 and cultured for six months.The mean fish yield of the adopted ponds was 795.79 kg ha-1 in 6 months against the pre-adoption production level of378.95 kg ha-1. Involvement of rural women in polyculture of carps proved to be economically beneficial and it is hoped thatthis would go a long way in strengthening their livelihood